Metrics and case studies for evaluting engineering designs - Moody, Jay Alan (Prentice-Hall international series in industrial and systems engineering, 1997)
"Metrics and Case Studies for Evaluating Engineering Designs considers four principal metrics for system design:" "Design Difficulty - Some projects do not immediately reveal their complexity. Taking some time to assess the true intricacy of each situation at the outset allows you to plan appropriately from the beginning." "Required Resources - An accurate understanding of the materials and personnel needed to fulfill your goals is another keystone of good planning." "Systems Engineering Efficacy - As projects get more sophisticated, the impact of systems structure becomes more and more important for success." "Developmental Environment - Both technology and organizational politics affect the progress of any project. Knowing your environment allows you to identify risks before they endanger your project." "Metrics and Case Studies for Evaluating Engineering Designs applies these metrics to 30 real-life case studies. Drawn from the authors' experience in industry and teaching, each case illustrates one or more of the essentials in action. Moving from simple to complex systems, the book shows how readers can apply these theories to develop individual metrics tailored to their own organizations." "This common-sense approach does not require readers to understand complicated mathematics or statistical models. The authors' straightforward style makes this book ideal reading for executives in business and government who need to evaluate complex programs without having a heavy technical background. Students in all engineering disciplines can also benefit from this practical, inventive guide."--BOOK JACKET.